EFEKTIVITAS MODEL PROJECT BASED LEARNING BERBASIS GAMIFIKASI UNTUK MENDUKUNG PEMAHAMAN KONSEP MATERI STATISTIKA SISWA SMP - Miftahudin; Rahayuningsih, Suesthi; Feriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conceptual understanding is a crucial foundation in mathematics learning, including in statistics, but observations and interviews at MTs. Manba'ul Ulum Japanan Kemlagi indicate that students' conceptual understanding remains low due to the predominance of conventional lecture-based teaching approaches that do not actively engage students. This study aims to determine the effectiveness of a gamification based Project Based Learning model in supporting junior high school students' understanding of statistical concepts, assessed through teacher activities, student activities, and conceptual understanding. This study employs a descriptive quantitative approach using a One Shot Case Study design. The sample was determined using purposive sampling, namely 20 eighth-grade students of Class VIII B at MTs. Manba'ul Ulum Japanan Kemlagi. Data were collected using observation sheets for teacher and student activities and a conceptual understanding test. The results showed that teacher activities scored 92.6% (very good category), student activities averaged 83.3% (good category), and the conceptual understanding test showed that 16 of 20 students achieved at least the good category, with a classical mastery rate of 80%. All three aspects met the established effectiveness criteria; therefore, the gamification based Project Based Learning model is effective in supporting junior high school students' understanding of statistical concepts.